1983
DOI: 10.1002/dev.420160207
|View full text |Cite
|
Sign up to set email alerts
|

The ontogeny of delta‐9‐tetrahydrocannabinol responsiveness in the rabbit

Abstract: An autosomal recessive condition (thc/thc) in our closed colony of New Zealand White rabbits (Uaz:NZW-thc) results in nonfatal, behavioral convulsions following intravenous (i.v.) injections of delta-9-tetrahydrocannabinol (THC) and other psychoactive cannabinoids of marijuana. The ontogeny of the convulsive response was evaluated in potential THC-seizure-susceptible (SS) rabbits from postnatal Days (PN) 15-548. Ages of nonsusceptibility (PN 15-23), partial susceptibility (PN 24-38), and complete susceptibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1984
1984
2006
2006

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…As in human studies, cannabinoids were found to exert both anti-and proconvulsive activity in animal models of epilepsy, largely depending on the stimulus applied to induce seizures (chemical, electrical, light, or fever) and the species used (Johnson et al, 1975;Ten Ham et al, 1975;Wada et al, 1975a,b;Corcoran et al, 1978;Chiu et al, 1979;Duncan and Dagirmanjian, 1979;Fish et al, 1981;Karler and Turkanis, 1981;Colasanti et al, 1982;Fish and Consroe, 1983;Karler et al, 1984Karler et al, , 1986Consroe and Mechoulam, 1987;Pertwee et al, 1991;Hayase et al, 2001a,b;reviewed in Gordon and Devinsky, 2001;Lutz, 2004).…”
mentioning
confidence: 99%
“…As in human studies, cannabinoids were found to exert both anti-and proconvulsive activity in animal models of epilepsy, largely depending on the stimulus applied to induce seizures (chemical, electrical, light, or fever) and the species used (Johnson et al, 1975;Ten Ham et al, 1975;Wada et al, 1975a,b;Corcoran et al, 1978;Chiu et al, 1979;Duncan and Dagirmanjian, 1979;Fish et al, 1981;Karler and Turkanis, 1981;Colasanti et al, 1982;Fish and Consroe, 1983;Karler et al, 1984Karler et al, , 1986Consroe and Mechoulam, 1987;Pertwee et al, 1991;Hayase et al, 2001a,b;reviewed in Gordon and Devinsky, 2001;Lutz, 2004).…”
mentioning
confidence: 99%